Strategi Pengembangan Bauran Pemasaran Dengan Analisis Swot Pada Koperasi Petani Kopi Arabika di Indonesia - Boris Kaido (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2024)
Coffee is an important global agricultural commodity. Jambi Province only has one special Arabica coffee production center in Kerinci Regency. Cooperatives are very important in supporting the economy of small farmers as collectors of farmers' coffee harvests. However, there are various challenges, especially in developing marketing areas so that cooperatives can continue to operate. The aim of this research is to create a marketing strategy for Arabica specialty coffee cooperatives. Data was collected through in-depth interviews with cooperative leaders, using purposive sampling for a case study of the Alam Kerinci cooperative, which is the largest specialized Arabica cooperative in Kerinci district, Indonesia. This research applies the 4P marketing mix theory and SWOT analysis to examine the problems raised and develop strategies for developing cooperative marketing in the future. Evidence shows that cooperatives have implemented marketing mix strategies effectively. SWOT calculations, IFAS analysis (X = 0.95), and EFAS (Y = 0.53) show that the cooperative is in quadrant I which is a very profitable position for implementing growth-oriented strategies to support the development and expansion of aggressive cooperative marketing. . This study shows that cooperatives have the potential to expand marketing, as shown by SWOT analysis and quadrant identification.